Village Financial Management Through Good Governance: Challenges Faced by Village Governments in Managing Village Funds - Ahmad Suprastiyo; Januwarso, Arief; Junadi, Junadi (Journal of Social and Policy Issues, 2025)
The purpose of this study is to analyze the financial management model of villages through the principles of good governance. The research methodology uses a qualitative method with a case study design, data collection through observation techniques, in-depth interviews, and document analysis. Data validity is ensured through triangulation of sources and data collection methods. The research informants consist of 17 individuals, including the Village Secretary, Village Treasurer, Village Council, Village Consultative Body, Department of Village Community Empowerment, Inspectorate, and Village Community. Data analysis includes data collection, data display, data condensation, and conclusion drawing/verification. The research findings indicate that accountability is in place, but it is not accompanied by a strong commitment from the Village Head. Community participation focuses on the results of development rather than monitoring or supervising budget use. The use of the village website for financial transparency is still minimal. In terms of the rule of law, there is still non-compliance with regulations in village financial management, necessitating the concept of preventive oversight. The limitations of this study are related to the key informant, the Village Head of Kapas, who could not be interviewed due to legal proceedings, and the study did not include aspects of equality, vision, strategy, responsiveness, and consensus-oriented principles in village financial management. These limitations can serve as recommendations for future research. The implications of this study are the development of concepts for financial management in village governance in Indonesia